Intracellular accumulation of extracellular proteins by pleiotropic export mutants of Aeromonas hydrophila. - Howard, S P (1983)
Pleiotropic export mutants of Aeromonas hydrophila were obtained which are unable to release protease, hemolysin, and glycerophospholipid:cholesterol acyltransferase. The synthesis of the proteins was not impaired; they were accumulated in active forms inside the mutant cells. The hemolysin could be isolated from cell contents by immunoprecipitation in a form with the same apparent molecular weight as the wild-type extracellular product, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Because both the protease and the hemolysin could be released from the mutant cells by osmotic shock, it was concluded that they were accumulated in the periplasmic space. Some mutants were missing two major outer membrane proteins, both of which reappeared in revertants with the wild-type excretory phenotype. Another mutant class had a normal outer membrane protein profile. That two different mutant classes could be obtained indicates that at least two gene products may be needed for export after protein translocation through the inner membrane. The accumulation of proteins which can be released by osmotic shock suggests that the periplasm may be part of the normal route for protein export.